Learning from Young People Engaged in Climate Activism: The Potential of Collectivizing Despair and Hope. (November 2019) - Nairn, Karen
Hope takes on particular significance at this historical moment, which is defined by the prospect of a climate-altered future. Young people (aged 18–29) from climate action groups in New Zealand were interviewed about how they perceived the future. Deploying a unique combination of conceptual tools and in-depth analysis of a small set of interviews, I explore young New Zealanders' complex relationships with despair and hope. Paulo Freire claimed his despair as a young man 'educated' what emerged as hope. I extend Freire's concept in two ways by considering: (a) how hope might also 'educate' despair and (b) how hope and despair might operate at a collective level, drawing on Rosemary Randall's psychotherapeutic analysis of societal responses to climate change. Participants identified collective processes as generating hope. Collectivizing hope and despair is important so that young people do not feel climate change is only their burden to solve.